2002
DOI: 10.1080/1360786021000007009
|View full text |Cite
|
Sign up to set email alerts
|

Televisits: Sustaining long distance family relationships among institutionalized elders through technology

Abstract: The role of social support in the health of older persons is well documented. This support is particularly important for isolated nursing home residents. The purpose of this study was to test the feasibility of using low-cost videophones to enhance communication between nursing home residents and their families. Ten pairs of residents and family members received videophones and engaged in regular televisits for six months. All participants completed brief survey instruments prior to and after the study period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
70
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 0 publications
6
70
1
Order By: Relevance
“…This, in turn, would deliver closer social support for isolated patients (Mickus & Luz, 2002). In general, Mickus and Luz's (2002) study suggested that videophone family interaction technology could be successfully used in nursing homes by selected residents to enhance social interactions and to close the distance between residents and their family members. Note that the "videophone" and the "televisitation" terms are interchangeable.…”
Section: Applications and Benefits Of Televisitation In Geriatricsmentioning
confidence: 99%
See 4 more Smart Citations
“…This, in turn, would deliver closer social support for isolated patients (Mickus & Luz, 2002). In general, Mickus and Luz's (2002) study suggested that videophone family interaction technology could be successfully used in nursing homes by selected residents to enhance social interactions and to close the distance between residents and their family members. Note that the "videophone" and the "televisitation" terms are interchangeable.…”
Section: Applications and Benefits Of Televisitation In Geriatricsmentioning
confidence: 99%
“…Patients and healthcare providers are the main users of teleconferencing in the area of geriatrics (Mickus & Luz, 2002). However, there has been virtually no research on the usage of teleconferencing for social support -linking patients with their families or significant others.…”
Section: Applications and Benefits Of Televisitation In Geriatricsmentioning
confidence: 99%
See 3 more Smart Citations